1996
DOI: 10.1007/bf00165652
|View full text |Cite
|
Sign up to set email alerts
|

Meningioma in the pediatric population

Abstract: Pediatric meningiomas are rare. They are usually seen in association with neurofibromatosis type 2 (NF-2) or following radiation therapy. The tumors are more frequently intraventricular, cystic, and infratentorial than are those in adult patients. Pathologically they are more histologically aggressive than in adults and tend to recur more frequently. Complete resection is the surgical goal. The treatment of subtotally resected meningiomas, particularly in NF-2, remains controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
7

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 28 publications
(54 reference statements)
1
55
0
7
Order By: Relevance
“…While most pediatric meningiomas are supratentorial and extraventricular, the infratentorial, intraorbital, and intraventricular locations are more commonly seen in children than adults [1, 2, 4, 7,11,12,13]. In our series, 6 patients (30%) had meningiomas in the posterior fossa, orbit, or ventricle.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…While most pediatric meningiomas are supratentorial and extraventricular, the infratentorial, intraorbital, and intraventricular locations are more commonly seen in children than adults [1, 2, 4, 7,11,12,13]. In our series, 6 patients (30%) had meningiomas in the posterior fossa, orbit, or ventricle.…”
Section: Discussionmentioning
confidence: 78%
“…Modan et al[ 6] studied 11,000 children who had been irradiated for tinea capitis and found a fourfold increased risk of meningioma. The prevalence of NF-2 in pediatric patients with meningioma has been shown to be 25–40% [1, 2,7,8,9,10]. Patients with spontaneously arising meningiomas appear to have tumors distinct from those with radiation-induced meningiomas or those associated with NF-2, in that those patients with spontaneously arising meningiomas were younger at the time of diagnosis, were more likely to be female, and had tumors that were more likely to recur and to be malignant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A localização destes tumores nos ventrículos, mais rara nos adultos, é bem mais frequente nas crianças, sendo que cerca de 15 a 17% dos meningiomas na infância se localizam no sistema ventricular, mais comumente no átrio do ventrículo lateral. A teoria mais aceita sobre a origem destas lesões é a de que elas surgem de células meningoteliais do estroma do plexo coróide [1][2][3][4][5][6][11][12][13] .…”
Section: Discussionunclassified
“…No adulto, tais lesões representam cerca de 20% dos tumores intracranianos. A localização intraventricular dos meningiomas é rara, embora na divisão dos casos por faixa etária, seja mais comum em crianças (15 a 17%) do que em adultos (1,6%), sendo os ventrículos laterais a localização mais frequente [1][2][3][4][5][6][7][8][9] …”
unclassified